Value Co-Creation for E-Government Services in Small Island Developing Nations: A Case Study - Wilford Gibson Lol; Krassie Petrova; Sarita Pais (Information, 2025)
The adoption of e-government services in Small Island Developing Nations (SIDNs) aims to enhance public service efficiency, inclusiveness, and quality. However, e-government service development in SIDNs faces some significant constraints, including limited resources, geographical isolation, low digital literacy levels, and inadequate technological infrastructure. This study investigates value co-creation approaches in e-government service, aiming to identify specific value co-creation processes and methods to support sustainable e-government initiatives in SIDN settings. The study applies a qualitative approach; based on the thematic analysis of interviews with government stakeholders, it identifies contextual factors and conditions that influence e-government value co-creation processes in SIDNs and strategies for sustainable e-government service value co-creation. This study contributes a value co-creation framework that applies participatory design, agile development, collaborative governance, socio-technical thinking, and technology adaptation as methods for the design and implementation of flexible and inclusive e-government services that are responsive to local needs, resilient to challenges, and sustainable over time. The framework can be used by policymakers and practitioners to facilitate sustainable digital transformation in SIDNs through collaborative governance, active participation, and civic engagement with innovative technologies.